Relevansi Syariah dalam Pengembangan Model Pendidikan Islam Inklusif dan Humanis - Heru Susanto; Akhmad Jazuli Akhmad Jazuli Afandi2; Arie Sulistyawan (Prodi PAI Fakultas Tarbiyah IAI Sunan Giri Trenggalek, 2026)
This study aims to examine the relevance of sharia in developing an inclusive and humanistic model of Islamic education amid the dynamics of a modern, plural, and complex society. Sharia, as a system of values, is not only understood in its normative-legal dimension but also encompasses universal principles such as justice, compassion, public welfare, and respect for human dignity. This research employs a qualitative approach using a library research method, analyzing various classical and contemporary literatures related to the concepts of sharia, Islamic education, and the paradigms of inclusivity and humanism. The findings indicate that the values of sharia have strong relevance in constructing an Islamic educational model that is open, tolerant, and oriented toward the holistic development of human potential. The principles of maqāṣid al-sharī‘ah, particularly in preserving religion, life, intellect, lineage, and wealth, can serve as a foundation for formulating curricula, learning methods, and educational interactions that respect diversity and uphold human values. Thus, the integration of sharia into Islamic education not only strengthens Islamic identity but also fosters the creation of an inclusive, dialogical, and civilized educational environment. This study concludes that the development of an inclusive and humanistic Islamic education model based on sharia values is a necessity in addressing the challenges of globalization, as well as a solution for building a just and civilized civilization..